Pengaruh Debt To Asset Ratio (DAR) dan Fixed Asset Turnover (FATO) Terhadap Return On Asset (ROA) Pada PT Ciputra Development, Tbk - Anisaturrahmah, Anisaturrahmah; Nurhayati , Nurhayati; Muniarty, Puji (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
This study aims to analyze the effect of Debt to Asset Ratio (DAR) and Fixed Asset Turnover (FATO) on Return on Assets (ROA) at PT Ciputra Development Tbk. The data used were financial statements from 2016 to 2023, selected using purposive sampling. The analytical method applied was multiple linear regression, including classical assumption tests, t-test, F-test, and coefficient of determination, using SPSS software. The results indicate that DAR has no significant effect on ROA, and FATO also does not significantly affect ROA. Simultaneously, DAR and FATO do not significantly influence ROA, with a coefficient of determination of 54.6 percent. These findings suggest that the profitability of property companies is not solely determined by capital structure and fixed asset efficiency, but also by other factors such as cost efficiency, marketing strategies, project diversification, and macroeconomic conditions. The implications highlight the importance for management to balance debt utilization and optimize fixed asset usage in line with property business cycles, and for investors to consider additional financial and external indicators when assessing company performance.